2011
DOI: 10.1111/j.1095-8312.2011.01742.x
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic framework for the evolution of female polymorphism in anoles

Abstract: Female pattern polymorphisms (FPP) are striking, poorly understood, and a major challenge to evolutionary theory. We examined the evolution of FPP in anoline lizards in a phylogenetic context. Accordingly, we used comparative analyses that traced the evolution of female pattern polymorphism over historical time, and overlaid the historical pattern on the biogeographical distribution of current species. Comparative analyses used a maximum likelihood approach with variable rates of trait evolution. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 70 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…Sex‐specific colour polymorphisms associated with different life‐histories have been extensively documented in many different taxa, such as insects, isopods, molluscs, and vertebrates (Oliveira, Taborsky & Brockmann, ). Although the interest in FPP has increased substantially (Svensson et al ., ; Cox & Calsbeek, ; Ortega, López & Martín, ), a bias towards insect studies exists, and vertebrates have received less attention (Paemelaere, Guyer & Dobson, ). Colour polymorphism is a common phenomenon in lizards (Forsman & Shine, ; Sinervo, Svensson & Comendant, ; Vercken et al ., ), comprising a group with the most compelling examples of alternative reproductive strategies linked to different morphs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sex‐specific colour polymorphisms associated with different life‐histories have been extensively documented in many different taxa, such as insects, isopods, molluscs, and vertebrates (Oliveira, Taborsky & Brockmann, ). Although the interest in FPP has increased substantially (Svensson et al ., ; Cox & Calsbeek, ; Ortega, López & Martín, ), a bias towards insect studies exists, and vertebrates have received less attention (Paemelaere, Guyer & Dobson, ). Colour polymorphism is a common phenomenon in lizards (Forsman & Shine, ; Sinervo, Svensson & Comendant, ; Vercken et al ., ), comprising a group with the most compelling examples of alternative reproductive strategies linked to different morphs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several Anolis species present FPP where females within a population generally show two or three variations in melanin‐based mid‐dorsal patterns (i.e. a vertebral stripe, a diamond pattern or a dull pattern that resembles males; Calsbeek, Bonneaud & Smith, ; Paemelaere et al ., ), whereas males are usually the less patterned sex and are rarely striped. In addition, in the common lizard, Z. vivipara , the frequency of individuals with a reticulated dorsal pattern is higher in males than in females (Lepetz et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ancestral condition is likely to be absence of FPP, and it has been gained more frequently than lost, suggesting that it may be under selective pressures that favour its emergence and maintenance (Paemelaere et al, 2011a). Stamps & Gon (1983) suggested that predation on females is stronger because they are less agile and more nutritious, and FPP may arise as a type of protection against avian predators (Stamps & Gon, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…female pattern polymorphism, FPP). The latter has been documented in a number of anole species, and several studies have suggested a link between habitat and female polymorphism in dorsal pattern (Cox & Calsbeek, 2011;Paemelaere, Guyer & Dobson, 2011a). Both sexual dimorphism and FPP have evolved multiple times in anoles (Butler, Schoener & Losos, 2000;Butler & Losos, 2002;Butler, Sawyer & Losos, 2007;Paemelaere et al, 2011a), making it an ideal system to test which conditions can influence the evolution of variation in dorsal pattern within species.…”
Section: Introductionmentioning
confidence: 99%